Kepastian Hukum Hibah Wasiat atas Tanah kepada Ahli Waris yang Bersengketa dalam Perspektif Hukum Perdata - Pangeran J. M. Somalay; Anriz N. Halim; Khoirul Anwar (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
Disputes over testamentary grants of land frequently arise due to unclear execution and insufficient protection of other heirs’ rights, leading to legal uncertainty. This study aims to examine the legal consequences of disputed testamentary grants of land and to analyze the realization of legal certainty within such disputes from a civil law perspective. The research employs a normative juridical method using statutory, conceptual, analytical, and case approaches. Legal materials consist of primary, secondary, and tertiary sources, analyzed through grammatical and systematic interpretation, supported by the theories of legal certainty and legal consequences. The results indicate that disputed testamentary grants may result in the degradation of evidentiary strength of the deed, potential claims for annulment by disadvantaged heirs, and uncertainty regarding land ownership status. Legal certainty can be achieved through the proper drafting of testamentary deeds in accordance with legal procedures, clear formulation of the grant, registration of land title transfer, and the protection of heirs’ compulsory shares. This study contributes by emphasizing the importance of integrating procedural compliance with substantive fairness to minimize inheritance disputes and strengthen legal certainty in land-related testamentary practices.